Identifikasi Faktor Penentu Perubahan Tingkat Pengangguran di Kabupaten/Kota Provinsi Banten - Edah Jubaedah; Anita Amelia (Universitas Pasundan, 2022)
This study aims to identify the determinants of changes in the unemployment rate in the City/Province of Banten as the object of research. Researchers used panel data regression analysis method through Fixed Effect Model (FEM). This method will explain how the influence of the minimum wage, investment, economic growth, human development index, and the number of workers on changes in the unemployment rate in the Regency/City of Banten Province in the period 2011-2018. The results of testing and data processing show that there are variations in the Regency/City of Banten Province in 2011-2018. The results of simultaneous data processing, all independent variables, namely the minimum wage, investment, economic growth, human development index, and the number of workers together have a significant effect on the open unemployment rate in the Regency/City of Banten Province in 2011-2018. Meanwhile, partially the minimum wage variable has a significant effect, but investment, economic growth, the human development index, and the number of workers have an insignificant effect on the unemployment rate in the Regency/City of Banten Province in 2011-2018.